Turning waste management into a carbon neutral activity: practical demonstration in a medium-sized European city - Fernández Braña, Álvaro (2022)
A Life Cycle Assessment (LCA) with focus on carbon footprint, followed by Life Cycle Costing (LCC) of municipal solid waste (MSW) management were conducted in a residential area of a medium-sized European city of 80,000 inhabitants. The initial results showed high environmental impacts and lack of economic sustainability, due to the high amounts of waste landfilled, the low extent of separate collection, low performance of mechanicalbiological treatment as well as absence from alternatives to landfilling of non-recyclable materials. Taking this result as a baseline scenario, three improvement.s were tested with the aim of turning the carbon footprint of the local MSW management system into a neutral value: (i) increased separate collection of recyclables, (ii) enhanced biogas production and (iii) refuse-derived fuel (RDF) production. Successively adding the improvements, three alternative improved scenarios were defined, until reaching a negative carbon footprint, meaning that an optimised system would avoid GHG emissions. The proposed changes were sufficient to achieve carbon neutrality, as well as reduce overall environmental impacts, but were not enough for achieving economic sustainability due to the great influence of collection costs, especially for separate collection. It was concluded that by using an adequate combination of several treatment options and increasing the separate collection of recyclable materials it is possible to turn MSW management into a carbon neutral activity as well as improve its economic balance.